A259 HIGH-FAT/HIGH-CHOLESTEROL DIETS PREDISPOSE THE HOST TO EXACERBATED ENTERIC INFECTIONS. (26th February 2020) - Valdes, J; Armas, A; Gagné Sansfaçon, J; Reyes-Nicolas, V; Rivard, N; Marrero, G; Perreault, N; Menendez, A
Abstract: Background: High-fat/high-cholesterol diets are a well established risk factor for cardiovascular and metabolic diseases, given their propensity to trigger perturbations ranging from altering whole body lipid profile to the induction of intestinal dysbiosis. However much less is known about their effects on the host's susceptibility to enteric infections. Aims: To determine the effects of high-fat/high-cholesterol diets over the host's susceptibility to enteric bacterial infections and identify the underlying molecular mechanisms. Methods: C57BL/6 mice were given two different high-fat/high-cholesterol diets; HFHC (40% kcal fat, 1.25% cholesterol) or HFHCC (40% kcal fat, 1.25% cholesterol, 0.5% sodium cholate) and a control, normal diet (ND, 10% kcal fat, 0% cholesterol, 0% sodium cholate). After four weeks of administration, animals were euthanized and colonic tissue samples taken for histology, immunofluorescence, gene expression analyses, total protein lysates and microbiome sequencing (16S). A separated group of animals was gavaged with FITC-dextran to measure intestinal permeability. Mice fed with the diets for three weeks were infected with ~5x10 8 cfu of Citrobacter rodentium DBS100/StrpR by oral gavage, and kept on the corresponding diets after the infections. Bacterial shedding in the feces was followed for up to 30 days after infection. Results: Administration of the HFHC and HFHCC diets caused an increase in intestinal permeability. Colonic sections stained with H&E and alcian blue evidenced a decreased in the number of mucin-filled goblet cells and a thinner mucus layer, suggesting a defect in the assembly and/or stability of the mucus layer. Expression analyses revealed a drop in the mRNA levels of Muc1 and Muc2, suggesting reduced mucin production. The concentration of IgA was slightly reduced in colon lysates and the transcript levels of the antimicrobial peptide genes Ang4, Leap2 and Cramp were also significantly reduced. Immunofluorescent microscopy showed that goblet cell granules of HFHC- and HFHCC-fed mice were devoid of Relmβ and Tff3, indicating defective production of those two factors critical for intestinal epithelial defense and homeostasis. Collectively, our results suggest that HFHC and HFHCC diets induce differentiation and functional defects in goblet cells. Fecal shedding of C. rodentium showed an increased bacterial burden in HFHC- and HFHCC-fed animals, indicating a more aggressive bacterial infection, accompanied by increased epithelial damage. Conclusions: Consumption of high-fat/high cholesterol diets perturb the colonic homeostasis and alter intestinal defenses and the integrity of the intestinal barrier, predisposing the host to a higher susceptibility to enteric infections. Funding Agencies: CIHRNSERC